Product Innovation Of Noodles With Water Lentil Ingredients - Kurniawan, Taufiq; Ishak, Riani Prihatini; Widi Rangan, Ariatma Gracia (Universitas Negeri Padang, 2022)
People who are aware of the importance of quality of life are more likely to seek out natural food products in order to maintain their health. Natural food products derived from various plants can trigger curiosity and exploration while adding variety. One of the natural food products from this group is water lentils, commonly called duckweed.This research was conducted to find out whether water lentils, which are now available in the form of protein powder, can be developed into noodles that are suitable for serving a group of people with a healthy lifestyle. This study used an experimental design method approach. The researcher made water lentil noodles by modifying the egg noodle recipe. Products that have been successfully made will be presented to 15 semi-trained panelists who have a level of health awareness. The results of the hedonic test from the panelists showed that the water lentil noodles developed by the researchers were more preferable to ordinary egg noodles. In addition, the results of the different tests using the Mann-Whitney U method yielded significant differences in values between ordinary egg noodles and noodles with water lentils as filler. Noodles filled with water lentils have advantages in terms of appearance, texture, taste, and aroma, meaning that overall, all aspects of noodles filled with water lentils are preferred over ordinary egg noodles